Interactive methods of teaching Turkish as a foreign language - Aбуовa, А. (Journal of Oriental Studies, 2018)
This article is about learning Turkish language as a foreign language effectively through interactive methods. Including in it, there are free and easy ways to teach the Turkish language through the role play and business games. Also described knowledge of games and their types.